Contribution des données paléométallurgiques à l’histoire des sociétés ouest-africaines durant les royaumes de Ghâna, Mâli, Gao et Mossi - Caroline Robion-Brunner (Afriques)
In sub-Sahelian Africa, ironmaking is the oldest, most widespread and most important metallurgy that has been practised. Its trajectory, which is therefore long term – at least three millennia – declines with the importation of European iron from the 15th century and ends in the early 20th century. In the medieval period, when urbanisation, trans-Saharan trade, the arrival of Islam, and the founding and succession of kingdoms took place, iron production and use became widespread. This metal is no longer rare, and for several centuries it has replaced stone for agricultural and craft tools. It is traded in raw form or already transformed into objects. But what is the real place of this human activity in the development of societies? Is it central or peripheral? Is it an economic, political or societal issue for the powers that be? Does the place of iron production differ according to the type of political regime?Beyond the analysis of strictly technical questions related to iron production, paleometallurgy allows us to address more general questions in an original way. Fluctuations in the production and consumption of metals and metal objects offer the opportunity to question the needs of a population and thus to approach demography and settlement dynamics. The location of the production sites of raw materials, raw or manufactured products reflects the system of networks and control in which technical activities and exchanges take place. The circuits, the nature of the products and the identity of the actors of this activity can then be reconstructed.In this paper, a research project will be presented with the aim of collecting all the archaeological occurrences on the production and use of iron in order to re-interrogate, century after century, the relationship between the production of iron and the different political hegemonies that have crossed time and space. Using retrospective maps, we will follow the impact of the iron industry on the lives and activities of medieval populations. This re-exploitation of archaeological data will also make it possible to visualise the geographical, chronological and methodological gaps to be filled in order to fully achieve the restitution of the history of iron. In order to test the validity and relevance of the approach, we delimited a study area. This covers 1.5 million km2 and includes part of Mali, Burkina Faso, Ghana, Togo and Benin. In this area and in this article, we will attempt to understand more specifically the successive issues of the relationship between the iron industry and the West African kingdoms of Ghana, Mali, Songhay, Gao and Mossi.